Dermatokinetics of therapeutic agents - Murthy, S. Narasimha (Sathyanarayana Narasimha), 1971- (Boca Raton : Taylor & Francis, 2011)
'Novel drug delivery technologies strive to bypass challenging biological layers to elicit desired pharmacological activity. The skin, one of our key defensive barriers, is imperfect, and may allow certain topically applied substances or toxins to pass. The dermatokinetics of a drug determines the efficacy of treatment of skin disorders. Presenting the first comprehensive reference on this important area of research, Dermatokinetics of Therapeutic Agents includes a general overview of the theoretical as well as practical aspects of dermatokinetics and addresses the impact of nature of a drug delivery system on the dermatokinetics of drugs. Chapters and illustrations cover the introductory aspects significance, methods, and models used in dermatokinetic studies of therapeutic agents.Topics include: Theoretical Models for Dermatokinetics of Therapeutic Agents; Drug Delivery Approaches to Modulate Dermatokinetics of Drugs; Conventional Methods of Cutaneous Drug Sampling; Cutaneous Microdialysis; Sampling Substrates by Skin Permeabilization; Spectroscopic Techniques in Dermatokinetics Studies; Regulatory Perspective of Dermatokinetic Studies'--Provided by publisher.
Keywords: Administration, Cutaneous; Drug delivery systems -- methods; Skin absorption; Skin Diseases -- drug therapy